A New Insight into Ultrastable Zn Metal Batteries Enabled by In Situ Built Multifunctional Metallic Interphase. (7th November 2021) - Ouyang, Kefeng; Ma, Dingtao; Zhao, Ning; Wang, Yanyi; Yang, Ming; Mi, Hongwei; Sun, Lingna; He, Chuanxin; Zhang, Peixin
Abstract: Dendrite growth and parasitic side reactions are thorny issues that seriously damage the anode–electrolyte interface during Zn plating/stripping process, leading to uncontrollable Zn deposition and restraining application of aqueous Zn‐ion batteries (AZIBs). Here, a unique facile strategy to in situ build indium (In) metal interphase on the Zn anode is first proposed. The combination of experimental and theoretical investigations demonstrate that such metallic interphase prevents the hydrogen evolution reaction (HER) and Zn corrosion, and guides preferential growth along the Zn(002) plane to achieve smooth Zn deposition. As a result, the modified Zn anodes achieve the ultrahigh cumulative capacities of 5600 and 5000 mAh cm −2 at the high current densities of 2 and 5 mA cm −2, respectively, demonstrating an ultrastable plating/stripping behavior. More encouragingly, the rate performance and cyclic stability of the Zn–V2 O5 battery with the electrolyte additive can still deliver a specific capacity of 383.6 mAh g −1 after 5000 cycles at the high current density of 5 A g −1 . The strategy presented here as well as the in‐depth understanding of modified mechanism can not only provide an effective solution to address the Zn anode concerns, but also deepen the understanding of AZIBs. Abstract : To address the dendrite growth and side reactions, this work first proposes a facile strategy for in situ built multifunctional metallic interphases via electrolyte modification. Systematic investigations confirm that ultrastable Zn anodes can be achieved in the modified electrolyte system, as well as significantly enhanced electrochemical performance of Zn–V2 O5 batteries.